The Phenomenon of Internal Audit Supervision in Fighting Corruption and Creating an Anti-Fraud Culture in Corporations in Indonesia - Mustika Prabaningrum Kusumawati; Ari Nur Rahman; Panzi Aulia Rahman (Asia Pacific Fraud Journal, 2022)
Indonesia was shocked by the disclosure of a scandal in a corruption case involving a prominent company engaged in aviation services. This is closely related to the public’s question regarding how and to what extent the internal audit function within a company can fight against corruption and create an anti-fraud culture within the company itself. In fact, the phenomenon of internal auditors in eradicating corruption and creating an anti-fraud culture in a corporation can create two sides of a knife with common interests. These interests are supported by one side of the internal auditor and another in terms of culture and regulations that are less supportive of creating anti-fraud and anti-corruption. Two main factors that weaken the internal auditors the lack of integrity due to conflicts of interest between internal auditors and company employees, and the lack of individual capabilities in the technological era. Various ways can be done by the Government and stakeholders, as regulators, to optimize the role of internal auditors in eradicating corruption and creating an anti-fraud culture.